Preparation method and application of flame-retardant sound-absorbing foaming material

By optimizing the material formula and preparation process, a flame-retardant sound-absorbing foam material with high open porosity and excellent sound absorption performance was prepared, which solved the problem of insufficient sound absorption and flame retardancy of existing polyolefin foam materials and achieved wide application in fire-safe places.

CN120623619AActive Publication Date: 2025-09-12HUIZHOU CHANGYUAN SPECIAL TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202511009887.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-22
Publication Date
2025-09-12
Estimated Expiration
2045-07-22

AI Technical Summary

Technical Problem

Existing polyolefin foam materials have deficiencies in sound absorption and flame retardancy, making it difficult to meet the demand for high-efficiency, lightweight, flame-retardant sound-absorbing materials in modern industry and construction.

Method used

By optimizing the material formula and preparation process, using polyolefin resin, polyolefin copolymer, rubber, foaming agent, flame retardant and other raw materials, combined with electron radiation cross-linking and foaming treatment, a flame retardant and sound-absorbing foam material with high open porosity and excellent sound absorption performance is prepared.

Benefits of technology

It achieves efficient sound absorption performance and UL94-HF1 level flame retardant performance, expanding the application range of the material in places with high fire safety requirements. The material also has a stable pore structure and good mechanical properties.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a flame-retardant sound-absorbing foaming material, and belongs to the technical field of polymer foaming. The raw materials comprise polyolefin resin, polystyrene, rubber, a foaming agent, a flame retardant, hollow glass beads, dicumyl peroxide, a foaming promoter and an antioxidant. The preparation process comprises the steps of internal mixing granulation, mixing granulation, extrusion molding, electron irradiation crosslinking, preheating foaming, secondary foaming and the like. Compared with the prior art, the foam material prepared by the invention has excellent mechanical properties, sound absorption performance and flame retardance, is suitable for rail transit, superstores, KTVs (Karaoke Television) and other places, and has a wide application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer foaming, and in particular to a preparation method and application of a flame-retardant sound-absorbing foaming material. Background Art

[0002] With the rapid development of the global economy, accelerated industrialization, and advancing urbanization, transportation, industrial production, and various large-scale infrastructure projects have grown rapidly. However, these advances have also brought about serious noise pollution problems. The high levels of noise generated by places like cars, high-speed trains, and large factories not only severely impact people's physical and mental health but also have numerous negative effects on the environment and ecosystems. Noise pollution has become a major issue that needs to be addressed in modern society.

[0003] Among the many noise control technologies, the use of sound-absorbing materials is a key tool. Traditional sound-absorbing materials primarily include glass fiber, rock wool, and foam plastics. However, these materials often suffer from high density, limited sound absorption, and flammability, making them difficult to meet the demand for efficient, lightweight, and flame-retardant sound-absorbing materials in modern industry and construction. In recent years, polyolefin foam materials have gradually attracted attention due to their excellent properties such as light weight, thermal insulation, heat preservation, corrosion resistance, and sound absorption. However, existing polyolefin foam materials mostly have closed-cell structures. While they offer excellent thermal insulation, they have poor sound absorption and insufficient flame retardancy, limiting their application in locations with high fire protection requirements, such as high-speed rail, large shopping malls, and automobiles.

[0004] To address these issues, researchers have conducted extensive research. For example, Chinese patent application publication number CN118480224 A discloses a lightweight, heat-insulating, sound-absorbing foam material and its preparation method. The material is prepared by mixing a polyolefin resin, a foaming agent, a flame retardant, and a foaming aid, followed by extrusion, radiation cross-linking, and foaming to produce a foam material with excellent mechanical properties. However, this invention still fails to fully address the shortcomings of polyolefin foam materials in terms of sound absorption and flame retardancy.

[0005] Furthermore, open-cell polyolefin foams, due to their interconnected pores, can effectively absorb sound waves and convert sound energy into heat, thereby achieving a noise reduction effect. However, these materials often suffer from unstable pore structures, poor mechanical properties, and insufficient flame retardancy, limiting their widespread application. Therefore, the development of polyolefin foams that combine excellent sound absorption, flame retardancy, and mechanical properties has become an urgent need in the relevant fields. Summary of the Invention

[0006] In order to address the deficiencies in the prior art, the present invention aims to provide a method for preparing and applying a flame-retardant sound-absorbing foam material. By optimizing the material formula and preparation process, the deficiencies in sound absorption and flame retardancy of existing polyolefin foam materials are addressed, providing an efficient and environmentally friendly solution for noise pollution control and fire safety.

[0007] In order to achieve the above-mentioned object of the invention, the present invention adopts the following technical solutions: A method for preparing a flame-retardant sound-absorbing foam material comprises the following raw materials in parts by weight: 20-60 parts of a polyolefin resin, 20-50 parts of a polyolefin copolymer, 10-30 parts of polystyrene, 5-20 parts of rubber, 1-20 parts of a foaming agent, 10-20 parts of a flame retardant, 0-10 parts of a filler, 1-5 parts of dicumyl peroxide, 0.5-10 parts of a foaming aid, and 0.5-3 parts of an antioxidant.

[0008] A method for preparing a flame retardant sound-absorbing foam material is as follows: S1. Mixing polyolefin copolymer and rubber in an internal mixer according to the formula to obtain a high-polarity elastomer masterbatch; S2, mixing and granulating a high-polarity elastomer masterbatch, a polyolefin resin, polystyrene, dicumyl peroxide, and an antioxidant to obtain a mixed masterbatch; S3, mixing the mixed masterbatch, filler, foaming agent, flame retardant, and foaming aid, and extruding to obtain a master roll; S4, cross-linking the mother roll by electron irradiation; S5, foaming the cross-linked mother roll in a horizontal furnace to obtain a closed-cell polyolefin foam material; S6. Perform secondary foaming on the closed-cell polyolefin foam material to obtain a flame-retardant and sound-absorbing foam material.

[0009] Preferably, the polyolefin resin is at least one of low-density polyethylene, high-density polyethylene, and polypropylene; and the polyolefin copolymer is ethylene-vinyl acetate copolymer.

[0010] The low-density polyethylene melt index is 0.5-4.0 g / 10 min, the high-density polyethylene melt index is 0.5-6.0 g / 10 min, the polypropylene melt index is 2-15 g / 10 min, and the ethylene-vinyl acetate copolymer melt index is 0.5-8.0 g / 10 min.

[0011] The rubber is at least one of ethylene propylene rubber, nitrile rubber, styrene butadiene rubber, and silicone rubber; the addition of rubber can promote cross-linking of the mother sheet, making the foaming material cells finer and more dense, and having better thermal insulation performance.

[0012] The foaming agent is at least one of azodicarbonamide, azobisisobutyronitrile, and barium azodicarboxylate.

[0013] The flame retardant is at least one of phosphate and melamine polyphosphate.

[0014] The filler is at least one of hollow glass microspheres, modified microspheres, and nano calcium carbonate; The particle size of the hollow glass microspheres is 50-100 μm. The hollow glass microspheres can increase the porosity of the material and effectively improve the sound absorption performance of the composite material. At the same time, a small amount of addition can effectively improve the mechanical properties of the material.

[0015] The foaming aids are zinc oxide and zinc stearate.

[0016] The antioxidant is a compound of DSTP and 1010, with a weight ratio of 2-4:1-3.

[0017] In step S1, the banburying temperature is 90-120°C.

[0018] In step S2, the granulation temperature is set at 120-150°C.

[0019] In step S3, the extrusion temperature is set to 120-150°C in zone 1, 122-155°C in zone 2, 125-155°C in zone 3, 130-160°C in zone 4, 130-160°C in zone 5, and 130-160°C in zone 6, and the die head temperature is set to 125-140°C.

[0020] In the step S4, the radiation cross-linking energy is 35-100 KeV. In step S5, the temperature of the preheating section is set to 140-160° C., the temperature of the foaming section is set to 180-250° C., and the foaming time is 1-5 minutes.

[0021] In step S6, the secondary foaming temperature is set to 180-220° C., and the foaming time is set to 0.5-3 minutes.

[0022] The preparation method of the modified microspheres is as follows: Z1. Adding silica-alumina sol, water and nitrogen-containing compound to a beaker under stirring, adjusting the pH to acidic with hydrochloric acid, then adding polyethylene glycol aqueous solution and stirring evenly, then pouring glutaraldehyde, stirring evenly and letting it stand, filtering to remove the supernatant, washing with water and anhydrous ethanol, and drying to obtain composite microspheres; placing the composite microspheres in a muffle furnace and heating and calcining to obtain porous microspheres; Z2. The porous microspheres are mixed and dispersed with anhydrous ethanol, a modifier and water are added, and the mixture is refluxed at a high temperature. The sample is collected, washed with anhydrous ethanol, and dried to obtain modified microspheres.

[0023] Preferably, the preparation method of the modified microspheres is as follows, in parts by weight: Z1. Add 0.3-0.8 parts of silica-alumina sol, 50-70 parts of water and 0.3-0.8 parts of nitrogen-containing compound to a beaker under stirring, adjust the pH to 1-3 with 8-12wt% hydrochloric acid, then add 1-3 parts of 4-6wt% polyethylene glycol aqueous solution, stir evenly, then pour in 0.5-1 parts of glutaraldehyde, stir evenly and let stand for 5-10 hours, filter to remove the supernatant, wash twice with water, wash once with anhydrous ethanol, and finally heat at 60-8 The composite microspheres were dried at 0°C to obtain composite microspheres; the composite microspheres were placed in a muffle furnace and calcined according to the following program: in the first stage, the temperature was increased from room temperature to 170-190°C at a rate of 7-9°C / min and kept at this temperature for 1-3 hours; in the second stage, the temperature was increased to 230-270°C at a rate of 4-6°C / min and kept at this temperature for 1-3 hours; in the third stage, the temperature was increased to 500-600°C at a rate of 2-4°C / min and kept at this temperature for 1-3 hours to obtain porous microspheres; Z2. Mix and disperse 0.3-0.8 parts of porous microspheres and 20-40 parts of anhydrous ethanol evenly, add 1-3 parts of modifier and 1-3 parts of water, reflux at 70-90°C for 1-5 hours, collect the sample, wash it three times with anhydrous ethanol, and dry it at 60-80°C for 5-24 hours to obtain modified microspheres.

[0024] The nitrogen-containing compound is at least one of urea, melamine and dicyandiamide.

[0025] The modifier is at least one of 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and diethylenetriaminopropyltrimethoxysilane.

[0026] The functions of each substance in the present invention are as follows: Polyolefin resin and polyolefin copolymer serve as matrix materials, providing the basic mechanical properties and thermal stability of the material.

[0027] Polystyrene improves the rigidity and processing properties of the material.

[0028] Rubber improves the elasticity and toughness of the material, promotes cross-linking of the mother sheet, and makes the cells of the foaming material finer and denser.

[0029] The foaming agent generates gas during the foaming process, forming a porous structure.

[0030] Flame retardants improve the flame retardant properties of materials so that they meet fire safety requirements.

[0031] Hollow glass microspheres increase the porosity of the material, enhance sound absorption performance, and improve mechanical properties.

[0032] Dicumyl peroxide is used as a cross-linking agent to promote the cross-linking reaction of the material and improve the thermal stability and mechanical properties of the material.

[0033] Foaming aids assist the decomposition of the foaming agent and improve the foaming effect.

[0034] Antioxidants prevent oxidative degradation of materials during processing and use, thereby extending the service life of the materials.

[0035] Modified microspheres improve the porosity and sound absorption performance of the material through surface modification.

[0036] The nitrogen-containing compound forms a stable structure during the high-temperature calcination process, provides physical support, and promotes the penetration of pores.

[0037] Modifiers optimize the interface properties and pore structure of materials through chemical bonding.

[0038] Compared with the existing technology, it has the following beneficial effects: 1) By optimizing the formula and process, this invention achieves a high open porosity and sound absorption coefficient. This characteristic gives it significant application advantages in places requiring efficient sound absorption, such as high-speed rail, large shopping malls, and KTVs.

[0039] 2) The flame retardant system and optimized formulation employed in this invention enable the foam material to achieve a UL94-HF1 flame retardancy rating. This enhanced flame retardancy significantly expands the material's application in applications requiring high fire safety standards, such as rail transit and automotive interiors, addressing the limited flame retardancy of traditional polyolefin foam materials.

[0040] 3) The foamed material produced through this specific preparation process not only exhibits excellent mechanical properties but also achieves a stable pore structure. This stable pore structure not only helps maintain efficient sound absorption but also avoids pore clogging or collapse, thereby extending the material's service life and improving its reliability in practical applications. DETAILED DESCRIPTION

[0041] Main sources of substances: Low-density polyethylene, olefin melt index is 1.9g / 10min, grade: LD662, brand: Yanshan Petrochemical.

[0042] High-density polyethylene, melt index is 3g / 10min, brand: FB0300, brand: South Korea LG.

[0043] Polystyrene, item number: 525, Guangdong Zhonghai Nanlian Energy Co., Ltd.

[0044] Ethylene-vinyl acetate copolymer, melt index is 2g / 10min, grade: EVA520F, brand: Toyo Soda.

[0045] Ethylene-vinyl acetate copolymer, melt index is 3.5g / 10min, brand: EVA11-3.5, brand: Sinopec.

[0046] Polypropylene, melt index is 3.5g / 10min, grade: 5014, brand: Korea Petrochemical.

[0047] Ethylene propylene rubber, brand: 2650C, manufacturer (origin): Lanxess, Germany.

[0048] Nitrile butadiene rubber, brand: 20231118, Jingjiang Kanggaote New Material Technology Co., Ltd.

[0049] The phosphate ester was triisobutyl phosphate, CAS No. 126-71-6, from Shandong Guohua Chemical Co., Ltd.

[0050] Melamine polyphosphate, CAS number: 15541-60-3, Jiangsu Runfeng Synthetic Technology Co., Ltd.

[0051] Hollow glass microspheres, porosity: 85%, specifications: 20-80 mesh, SiO2 content: 62%, Hebei Hengguang Mineral Products Co., Ltd.

[0052] Nano calcium carbonate, specification: 1250 mesh.

[0053] Melamine, product number: zy-1102, Zhongyan New Materials Co., Ltd.

[0054] Polyethylene glycol, model: PEG-400, brand: Russian Petrochemical.

[0055] Silica-alumina sol, model: FF-GL30W, particle size: 10-30 nm, Hangzhou Jiayou New Materials Co., Ltd.

[0056] PU foam sponge, item number: 20-65PPI, density: 20~35 (g / cm 3 ), Jiangmen Fengrun Daily Products Co., Ltd.

[0057] The remaining raw materials in the examples and comparative examples of the present invention are all commercially available products.

[0058] Example 1 A method for preparing a flame retardant sound-absorbing foam material is as follows, in parts by weight: S1. Formula composition: 40 parts of high-density polyethylene, 15 parts of polystyrene, 30 parts of ethylene-vinyl acetate copolymer, 10 parts of ethylene-propylene rubber, 12 parts of azodicarbonamide, 8 parts of flame retardant, wherein the flame retardant is a compound of phosphate and melamine polyphosphate in a weight ratio of 2:5, 0.5 parts of zinc oxide and 0.1 parts of zinc stearate, 1.5 parts of antioxidant, wherein the antioxidant is a compound of DSTP and 1010 in a weight ratio of 3:2, 1.5 parts of dicumyl peroxide, wherein the high-density polyethylene melt index is 3g / 10min, and the ethylene-vinyl acetate copolymer melt index is 2g / 10min; according to the formula composition, the ethylene-vinyl acetate copolymer and ethylene-propylene rubber are mixed and granulated in an internal mixer, and the mixing temperature is set to 100°C to obtain a high-polarity elastomer masterbatch; S2. Mixing and granulating a high-polarity elastomer masterbatch, high-density polyethylene, polystyrene, dicumyl peroxide, and an antioxidant, with the granulation temperature set at 125° C. to obtain a mixed masterbatch; S3. Mix the mixed masterbatch, azodicarbonamide, flame retardant, zinc oxide and zinc stearate, and extrude to obtain a master roll; set the temperatures of zones 1-6 of the extruder to 122°C, 125°C, 125°C, 128°C, 128°C and 130°C, and the die temperature to 125°C; S4, crosslinking the mother roll by electron irradiation, with the irradiation crosslinking energy being 45 KeV; S5, preheating and foaming the cross-linked mother roll, setting the preheating temperature to 150° C., the foaming temperature to 210° C., and the foaming time to 2 minutes to obtain a closed-cell polyolefin foam material; S6. Perform secondary foaming on the closed-cell polyolefin foam material at a foaming temperature of 185° C. and a foaming time of 1 minute to obtain a flame-retardant sound-absorbing foam material.

[0059] Example 2 A method for preparing a flame retardant sound-absorbing foam material is as follows, in parts by weight: S1. Formula composition: 50 parts of high-density polyethylene, 30 parts of ethylene-vinyl acetate copolymer, 20 parts of polystyrene, 15 parts of nitrile rubber, 13 parts of azodicarbonamide, 7 parts of flame retardant, wherein the flame retardant is a compound of phosphate and melamine polyphosphate in a weight ratio of 2:5, 1 part of zinc oxide and 0.5 parts of zinc stearate, 1.5 parts of antioxidant, wherein the antioxidant is a compound of DSTP and 1010 in a weight ratio of 3:2, 1.2 parts of dicumyl peroxide, wherein the melt index of high-density polyethylene is 3 g / 10min, and the melt index of ethylene-vinyl acetate copolymer is 2 g / 10min; according to the formula composition, ethylene-vinyl acetate copolymer and nitrile rubber are mixed and granulated in an internal mixer, and the mixing temperature is set to 100°C to obtain a high-polarity elastomer masterbatch; S2. Mixing and granulating a high-polarity elastomer masterbatch, high-density polyethylene, polystyrene, dicumyl peroxide, and an antioxidant, with the granulation temperature set at 125° C. to obtain a mixed masterbatch; S3. Mix the mixed masterbatch, azodicarbonamide, flame retardant, zinc oxide and zinc stearate, and extrude to obtain a master roll; set the temperatures of zones 1-6 of the extruder to 130° C., 132° C., 132° C., 136° C., 136° C., and 136° C., and the die temperature to 130° C.; S4, crosslinking the mother roll by electron irradiation, with the irradiation crosslinking energy being 80 KeV; S5, preheating and foaming the cross-linked mother roll, setting the preheating temperature to 150° C., the foaming temperature to 210° C., and the foaming time to 2 minutes to obtain a closed-cell polyolefin foam material; S6. Perform secondary foaming on the closed-cell polyolefin foam material at a foaming temperature of 185° C. and a foaming time of 1 minute to obtain a flame-retardant sound-absorbing foam material.

[0060] Example 3 A method for preparing a flame retardant sound-absorbing foam material is as follows, in parts by weight: S1. Formula composition: polyolefin resin includes 30 parts of low-density polyethylene and 20 parts of high-density polyethylene, 15 parts of polystyrene, 40 parts of ethylene-vinyl acetate copolymer, 10 parts of ethylene-propylene rubber, 12 parts of azodicarbonamide, 10 parts of flame retardant, wherein the flame retardant is a compound of phosphate and melamine polyphosphate in a weight ratio of 2:5, 5 parts of hollow glass microspheres, 1.5 parts of antioxidant, wherein the antioxidant is a compound of DSTP and 1010 in a weight ratio of 3:2, 0.5 parts of zinc oxide and 0.3 parts of zinc stearate, and 1.5 parts of dicumyl peroxide; wherein the melt index of low-density polyethylene is 1.9 g / 10 min, the melt index of high-density polyethylene is 3 g / 10 min, and the melt index of ethylene-vinyl acetate copolymer is 3.5 g / 10 min; according to the formula composition, ethylene-vinyl acetate copolymer and ethylene-propylene rubber are mixed and granulated in an internal mixer, and the mixing temperature is set to 100°C to obtain a high-polarity elastomer masterbatch; S2. Mixing and granulating a high-polarity elastomer masterbatch, a polyolefin resin, polystyrene, dicumyl peroxide, and an antioxidant, and setting the granulation temperature to 140° C. to obtain a mixed masterbatch; S3. Mix the mixed masterbatch, hollow glass microspheres, azodicarbonamide, flame retardant, zinc oxide and zinc stearate, and extrude them to obtain a master roll; the temperatures of zones 1-6 of the extruder are set to 126° C., 128° C., 130° C., 130° C., 132° C., and 132° C., and the die temperature is 128° C.; S4, crosslinking the mother roll by electron irradiation, with the irradiation crosslinking energy being 65KeV; S5, preheating and foaming the cross-linked mother roll, setting the preheating temperature to 150° C., the foaming temperature to 230° C., and the foaming time to 2 minutes to obtain a closed-cell polyolefin foam material; S6. The closed-cell polyolefin foam material is subjected to secondary foaming at a foaming temperature of 190° C. and a foaming time of 1 minute to obtain a flame-retardant sound-absorbing foam material.

[0061] Example 4 A method for preparing a flame retardant sound-absorbing foam material is as follows, in parts by weight: S1. Formula composition: polyolefin resin includes 20 parts of high-density polyethylene and 30 parts of polypropylene, 15 parts of polystyrene, 20 parts of ethylene-vinyl acetate copolymer, 5 parts of nitrile rubber, 10 parts of azodicarbonamide, 10 parts of flame retardant, the flame retardant is a compound of phosphate and melamine polyphosphate in a weight ratio of 2:5, 5 parts of hollow glass microspheres, 0.8 parts of zinc oxide and 0.5 parts of zinc stearate, 2 parts of antioxidant, the antioxidant is a compound of DSTP and 1010 in a weight ratio of 3:2, 1.3 parts of dicumyl peroxide, and 1 part of nano-calcium carbonate; the melt index of high-density polyethylene is 3g / 10min, the melt index of polypropylene is 3.5 g / 10min, and the melt index of ethylene-vinyl acetate copolymer is 3.5g / 10min; according to the formula composition, ethylene-vinyl acetate copolymer and nitrile rubber are mixed and granulated in an internal mixer, and the mixing temperature is set to 100°C to obtain a high-polarity elastomer masterbatch; S2. Mixing and granulating a high-polarity elastomer masterbatch, a polyolefin resin, polystyrene, dicumyl peroxide, and an antioxidant, and setting the granulation temperature to 140° C. to obtain a mixed masterbatch; S3. Mix the mixed masterbatch, hollow glass microspheres, nano-calcium carbonate, azodicarbonamide, flame retardant, zinc oxide and zinc stearate, and extrude them to obtain a master roll; the temperatures of zones 1-6 of the extruder are set to 155° C., 157° C., 160° C., 160° C., 160° C. and 165° C., and the die temperature is 145° C.; S4, crosslinking the mother roll by electron irradiation, with the irradiation crosslinking energy being 70 KeV; S5, preheating and foaming the cross-linked mother roll, setting the preheating temperature to 150° C., the foaming temperature to 230° C., and the foaming time to 2 minutes to obtain a closed-cell polyolefin foam material; S6. The closed-cell polyolefin foam material is subjected to secondary foaming at a foaming temperature of 200° C. and a foaming time of 1 minute to obtain a flame-retardant sound-absorbing foam material.

[0062] Example 5 A method for preparing a flame retardant sound-absorbing foam material is as follows, in parts by weight: S1. Formula composition: polyolefin resin includes 30 parts of low-density polyethylene and 20 parts of high-density polyethylene, 15 parts of polystyrene, 40 parts of ethylene-vinyl acetate copolymer, 10 parts of ethylene-propylene rubber, 12 parts of azodicarbonamide, 10 parts of flame retardant, wherein the flame retardant is a compound of phosphate and melamine polyphosphate in a weight ratio of 2:5, 5 parts of modified microspheres, 1.5 parts of antioxidant, wherein the antioxidant is a compound of DSTP and 1010 in a weight ratio of 3:2, 0.5 parts of zinc oxide and 0.3 parts of zinc stearate, and 1.5 parts of diisopropyl benzene peroxide; wherein the melt index of low-density polyethylene is 1.9 g / 10 min, and the melt index of ethylene-vinyl acetate copolymer is 3.5 g / 10 min; according to the formula composition, ethylene-vinyl acetate copolymer and ethylene-propylene rubber are mixed and granulated in an internal mixer, and the mixing temperature is set to 100°C to obtain a high-polarity elastomer masterbatch; S2. Mixing and granulating a high-polarity elastomer masterbatch, a polyolefin resin, polystyrene, dicumyl peroxide, and an antioxidant, and setting the granulation temperature to 140° C. to obtain a mixed masterbatch; S3. Mix the mixed masterbatch, modified microspheres, azodicarbonamide, flame retardant, zinc oxide and zinc stearate, and extrude them to obtain a master roll; the temperatures of zones 1-6 of the extruder are set to 126° C., 128° C., 130° C., 130° C., 132° C., and 132° C., and the die temperature is 128° C.; S4, crosslinking the mother roll by electron irradiation, with the irradiation crosslinking energy being 65KeV; S5, preheating and foaming the cross-linked mother roll, setting the preheating temperature to 150° C., the foaming temperature to 230° C., and the foaming time to 2 minutes to obtain a closed-cell polyolefin foam material; S6. The closed-cell polyolefin foam material is subjected to secondary foaming at a foaming temperature of 190° C. and a foaming time of 1 minute to obtain a flame-retardant sound-absorbing foam material.

[0063] The preparation method of the modified microspheres is as follows, in parts by weight: Z1. Under stirring conditions, 0.5 parts of silica-alumina sol, 60 parts of water and 0.5 parts of melamine were added to a beaker, the pH was adjusted to 2 with 10wt% hydrochloric acid, and then 2 parts of 5wt% polyethylene glycol aqueous solution were added and stirred evenly. Then, 0.85 parts of glutaraldehyde were poured into the mixture, stirred evenly and allowed to stand for 8 hours. The supernatant was removed by filtration, washed twice with water, washed once with anhydrous ethanol, and finally dried at 70°C to obtain composite microspheres; the composite microspheres were placed in a muffle furnace and calcined according to the following program: in the first stage, the temperature was increased from room temperature to 180°C at a rate of 8°C / min and kept warm for 2 hours; in the second stage, the temperature was increased to 250°C at a rate of 5°C / min and kept warm for 2 hours; in the third stage, the temperature was increased to 530°C at a rate of 3°C / min and kept warm for 2 hours to obtain porous microspheres; Z2. Mix and disperse 0.5 parts of porous microspheres and 30 parts of anhydrous ethanol evenly, add 2 parts of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and 2 parts of water, reflux at 80°C for 3 hours, collect the sample, wash it three times with anhydrous ethanol, and dry it at 70°C for 12 hours to obtain modified microspheres.

[0064] Example 6 The preparation method of a flame retardant sound absorbing foam material is basically the same as that of Example 5, the only difference being the preparation method of the modified microspheres.

[0065] The preparation method of the modified microspheres is as follows, in parts by weight: Z1. Under stirring conditions, 0.5 parts of silica-alumina sol, 60 parts of water and 0.5 parts of urea were added to a beaker, the pH was adjusted to 2 with 10wt% hydrochloric acid, and then 2 parts of 5wt% polyethylene glycol aqueous solution were added and stirred evenly. Then 0.85 parts of glutaraldehyde were poured into it, stirred evenly and allowed to stand for 8 hours, the supernatant was removed by filtration, washed twice with water, washed once with anhydrous ethanol, and finally dried at 70°C to obtain composite microspheres; the above-mentioned composite microspheres were placed in a muffle furnace and calcined according to the following program: in the first stage, the temperature was increased from room temperature to 180°C at a rate of 8°C / min and kept warm for 2 hours; in the second stage, the temperature was increased to 250°C at a rate of 5°C / min and kept warm for 2 hours; in the third stage, the temperature was increased to 530°C at a rate of 3°C / min and kept warm for 2 hours to obtain porous microspheres; Z2. Mix and disperse 0.5 parts of porous microspheres and 30 parts of anhydrous ethanol evenly, add 2 parts of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and 2 parts of water, reflux at 80°C for 3 hours, collect the sample, wash it three times with anhydrous ethanol, and dry it at 70°C for 12 hours to obtain modified microspheres.

[0066] Example 7 The preparation method of a flame retardant sound absorbing foam material is basically the same as that of Example 5, the only difference being the preparation method of the modified microspheres.

[0067] The preparation method of the modified microspheres is as follows, in parts by weight: Z1. Under stirring conditions, 0.5 parts of silica-alumina sol, 60 parts of water and 0.5 parts of dicyandiamide were added to a beaker, the pH was adjusted to 2 with 10wt% hydrochloric acid, and then 2 parts of 5wt% polyethylene glycol aqueous solution were added and stirred evenly. Then 0.85 parts of glutaraldehyde were poured into it, stirred evenly and allowed to stand for 8 hours, the supernatant was removed by filtration, washed twice with water, washed once with anhydrous ethanol, and finally dried at 70°C to obtain composite microspheres; the above-mentioned composite microspheres were placed in a muffle furnace and calcined according to the following program: in the first stage, the temperature was increased from room temperature to 180°C at a rate of 8°C / min and kept warm for 2 hours; in the second stage, the temperature was increased to 250°C at a rate of 5°C / min and kept warm for 2 hours; in the third stage, the temperature was increased to 530°C at a rate of 3°C / min and kept warm for 2 hours to obtain porous microspheres; Z2. Mix and disperse 0.5 parts of porous microspheres and 30 parts of anhydrous ethanol evenly, add 2 parts of N-(2-aminoethyl)-3-aminopropyltrimethoxysilane and 2 parts of water, reflux at 80°C for 3 hours, collect the sample, wash it three times with anhydrous ethanol, and dry it at 70°C for 12 hours to obtain modified microspheres.

[0068] Example 8 The preparation method of a flame retardant sound absorbing foam material is basically the same as that of Example 5, the only difference being the preparation method of the modified microspheres.

[0069] The preparation method of the modified microspheres is as follows, in parts by weight: Z1. Under stirring conditions, 0.5 parts of silica-alumina sol, 60 parts of water and 0.5 parts of melamine were added to a beaker, the pH was adjusted to 2 with 10wt% hydrochloric acid, and then 2 parts of 5wt% polyethylene glycol aqueous solution were added and stirred evenly. Then, 0.85 parts of glutaraldehyde were poured into the mixture, stirred evenly and allowed to stand for 8 hours. The supernatant was removed by filtration, washed twice with water, washed once with anhydrous ethanol, and finally dried at 70°C to obtain composite microspheres; the composite microspheres were placed in a muffle furnace and calcined according to the following program: in the first stage, the temperature was increased from room temperature to 180°C at a rate of 8°C / min and kept warm for 2 hours; in the second stage, the temperature was increased to 250°C at a rate of 5°C / min and kept warm for 2 hours; in the third stage, the temperature was increased to 530°C at a rate of 3°C / min and kept warm for 2 hours to obtain porous microspheres; Z2. Mix and disperse 0.5 parts of porous microspheres and 30 parts of anhydrous ethanol evenly, add 2 parts of 3-aminopropyltriethoxysilane and 2 parts of water, reflux at 80°C for 3 hours, collect the sample, wash it three times with anhydrous ethanol, and dry it at 70°C for 12 hours to obtain modified microspheres.

[0070] Example 9 The preparation method of a flame retardant sound absorbing foam material is basically the same as that of Example 5, the only difference being the preparation method of the modified microspheres.

[0071] The preparation method of the modified microspheres is as follows, in parts by weight: Z1. Under stirring conditions, 0.5 parts of silica-alumina sol, 60 parts of water and 0.5 parts of melamine were added to a beaker, the pH was adjusted to 2 with 10wt% hydrochloric acid, and then 2 parts of 5wt% polyethylene glycol aqueous solution were added and stirred evenly. Then, 0.85 parts of glutaraldehyde were poured into the mixture, stirred evenly and allowed to stand for 8 hours. The supernatant was removed by filtration, washed twice with water, washed once with anhydrous ethanol, and finally dried at 70°C to obtain composite microspheres; the composite microspheres were placed in a muffle furnace and calcined according to the following program: in the first stage, the temperature was increased from room temperature to 180°C at a rate of 8°C / min and kept warm for 2 hours; in the second stage, the temperature was increased to 250°C at a rate of 5°C / min and kept warm for 2 hours; in the third stage, the temperature was increased to 530°C at a rate of 3°C / min and kept warm for 2 hours to obtain porous microspheres; Z2. Mix and disperse 0.5 parts of porous microspheres and 30 parts of anhydrous ethanol evenly, add 2 parts of diethylenetriaminopropyltrimethoxysilane and 2 parts of water, reflux at 80°C for 3 hours, collect the sample, wash it three times with anhydrous ethanol, and dry it at 70°C for 12 hours to obtain modified microspheres.

[0072] Comparative Example 1 A preparation method of a flame-retardant sound-absorbing foam material is basically the same as that of Example 1, the only difference being that different raw materials are used. The raw materials are 100 parts of high-density polyethylene with a melt index of 3 g / 10 min, 15 parts of azodicarbonamide, and a flame retardant system of a composite flame retardant of aluminum hydroxide and magnesium hydroxide in a composite weight ratio of 4:1. The amount used is 10 parts, 1.5 parts of zinc oxide and 0.5 parts of zinc stearate, and 1 part of nano-calcium carbonate.

[0073] Comparative Example 2 Comparative Example 2 is PU foam sponge, commercially available.

[0074] Test Example 1 The performance indicators of Examples 1-9 and Comparative Examples 1-2 were tested using the following test methods: Apparent density: The test of apparent density is based on the test method described in GB / T 6343-2009 "Determination of apparent density of cellular plastics and rubber"; Tensile strength: The tensile strength test is based on the test method described in GB / T 6344-2008 "Flexible cellular polymeric materials - Determination of tensile strength and elongation at break"; Flame retardant grade: The flame retardant grade test is based on the test method recorded in the UL94 HF-1 "Horizontal combustion test of foam materials" test standard; Open cell rate: The open cell rate test is based on the test method described in ASTM D 2856-A "Standard method for determination of percentage of open cells in rigid foamed plastics using an air density meter"; Sound absorption coefficient: The sound absorption coefficient is determined based on the method described in ISO 354 "Acoustic sound absorption in reverberant rooms".

[0075] The test results are shown in the following table: <![CDATA[Apparent density (kg / m 3 > Tensile strength (MPa) Flame retardant grade Opening rate (%) Sound absorption coefficient Example 1 40 8.0 UL94-HF1 48 0.43 Example 2 50 6.0 UL94-HF1 55 0.47 Example 3 44 5.0 UL94-HF1 85 0.72 Example 4 42 4.8 UL94-HF1 78 0.65 Example 5 44 5.2 UL94-HF1 95 0.92 Example 6 46 5.1 UL94-HF1 68 0.78 Example 7 45 5.1 UL94-HF1 75 0.74 Example 8 44 4.8 UL94-HF1 85 0.85 Example 9 45 4.9 UL94-HF1 82 0.78 Comparative Example 1 40 10.0 UL94-HF1 12 0.18 Comparative Example 2 50 5.0 - 80 0.71 It can be seen from the data in the above table that the foam material prepared by the present invention has excellent flame retardant properties; from Examples 1-4, it can be seen that Example 3 and Example 4 have excellent sound absorption coefficients.

[0076] The test data from Examples 5-7 demonstrate that, under the conditions of immobilizing the modifier N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, melamine, thanks to its high-temperature stability (decomposition temperature > 350°C) and the rigid carbon nitride skeleton formed after calcination, achieves a 95% open porosity and a 0.92 sound absorption coefficient, significantly outperforming urea (68% open porosity / 0.78 sound absorption coefficient) and dicyandiamide (75% open porosity / 0.74 sound absorption coefficient). This may be due to the three-dimensional carbon nitride skeleton formed by calcining melamine at 530°C providing physical support during the foaming stage (230°C), promoting cell interconnection and optimizing sound wave scattering efficiency. However, the low-temperature decomposition of urea at 133°C leads to premature gas release during the preheating stage (150°C), resulting in uneven cell merging. The residual linear urea-formaldehyde structure suffers from poor thermal stability and prone to pore wall collapse. Dicyandiamide decomposes at 210°C at a slow gas release rate and generates toxic HCN, which weakens the carbon layer quality. The high-temperature rigid skeleton support effect of melamine is the key to its excellent open porosity and sound absorption performance, while urea and dicyandiamide cannot match its effect due to their decomposition defects.

[0077] Under the conditions of immobilizing a nitrogen-containing compound (melamine), the chemical structure of the modifier significantly influences the performance of flame-retardant, sound-absorbing foam materials. N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, through its primary (-NH2) and secondary (-NH-) amine groups, achieves a dual anchoring mechanism during the reflow process: the primary amine bonds to the silanol groups on the microsphere surface, while the secondary amine grafts to the phosphate groups (PO4³⁻) in the flame retardant, forming a stable PNC covalent network. This network not only optimizes acoustic impedance matching but also prevents pore clogging through the flexibility of the molecular chain, ensuring unimpeded multiple scattering paths for sound waves within the pores, thereby achieving the highest open porosity (95%) and sound absorption coefficient (0.92). In contrast, KH-550 (monoamino) suffers from a low grafting rate of a single primary amino group and poor compatibility with the polyolefin matrix, resulting in uneven microsphere dispersion, weak interfacial bonding, increased sound wave reflection at the pore walls, and reduced sound absorption efficiency (open porosity 85%, sound absorption coefficient 0.85). Diethylenetriaminopropyltrimethoxysilane, on the other hand, easily clogs pore channels, reducing the open porosity. Its rigid structure also hinders sound wave penetration, leading to a significant attenuation of the sound absorption coefficient in the high-frequency range (>5kHz) (open porosity 82%, sound absorption coefficient 0.78).

[0078] The above are all preferred examples of the present invention, and are not intended to limit the scope of protection of the present invention. Therefore, all formulations, processes, and principles of the present invention fall within the scope of protection of the present invention.

Claims

1. A method for preparing a flame retardant sound-absorbing foam material, characterized in that: Here’s how: S1. According to the formula composition, the polyolefin copolymer and rubber are mixed and granulated in an internal mixer to obtain a high-polarity elastomer masterbatch; S2, mixing and granulating a high-polarity elastomer masterbatch, a polyolefin resin, polystyrene, dicumyl peroxide, and an antioxidant to obtain a mixed masterbatch; S3, mixing the mixed masterbatch, filler, foaming agent, flame retardant, and foaming aid, and extruding to obtain a master roll; S4, cross-linking the mother roll by electron irradiation; S5, foaming the cross-linked mother roll in a horizontal furnace to obtain a closed-cell polyolefin foam material; S6, performing secondary foaming on the closed-cell polyolefin foam material to obtain a flame-retardant sound-absorbing foam material; The filler is at least one of hollow glass microspheres, modified microspheres, and nano calcium carbonate; The preparation method of the modified microspheres is as follows: Z1. Adding silica-alumina sol, water and nitrogen-containing compound to a beaker under stirring, adjusting the pH to acidic with hydrochloric acid, then adding polyethylene glycol aqueous solution and stirring evenly, then pouring glutaraldehyde, stirring evenly and letting it stand, filtering to remove the supernatant, washing with water and anhydrous ethanol, and drying to obtain composite microspheres; placing the composite microspheres in a muffle furnace and heating and calcining to obtain porous microspheres; Z2. The porous microspheres are mixed and dispersed with anhydrous ethanol, a modifier and water are added, and the mixture is refluxed at a high temperature. The sample is collected, washed with anhydrous ethanol, and dried to obtain modified microspheres.

2. The method for preparing a flame retardant sound absorbing foam material according to claim 1, wherein: The invention comprises the following raw materials in parts by weight: 20-60 parts of polyolefin resin, 20-50 parts of polyolefin copolymer, 10-30 parts of polystyrene, 5-20 parts of rubber, 1-20 parts of foaming agent, 10-20 parts of flame retardant, 0-10 parts of filler, 1-5 parts of dicumyl peroxide, 0.5-10 parts of foaming aid, and 0.5-3 parts of antioxidant; The nitrogen-containing compound is at least one of urea, melamine, and dicyandiamide; The modifier is at least one of 3-aminopropyltriethoxysilane, N-(2-aminoethyl)-3-aminopropyltrimethoxysilane, and diethylenetriaminopropyltrimethoxysilane.

3. The method for preparing a flame retardant sound absorbing foam material according to claim 1 or 2, wherein: The polyolefin resin is at least one of low-density polyethylene, high-density polyethylene, and polypropylene; the polyolefin copolymer is ethylene-vinyl acetate copolymer; The low-density polyethylene melt index is 0.5-4.0 g / 10 min, the high-density polyethylene melt index is 0.5-6.0 g / 10 min, the polypropylene melt index is 2-15 g / 10 min, and the ethylene-vinyl acetate copolymer melt index is 0.5-8.0 g / 10 min.

4. The method for preparing a flame retardant sound absorbing foam material according to claim 1 or 2, wherein: The rubber is at least one of ethylene propylene rubber, nitrile butadiene rubber, styrene butadiene rubber and silicone rubber.

5. The method for preparing the flame retardant sound absorbing foam material according to claim 1 or 2, wherein: The foaming agent is at least one of azodicarbonamide, azobisisobutyronitrile, and barium azodicarboxylate; The foaming aids are zinc oxide and zinc stearate.

6. The method for preparing a flame retardant sound absorbing foam material according to claim 1 or 2, wherein: The flame retardant is at least one of phosphate and melamine polyphosphate.

7. The method for preparing a flame retardant sound absorbing foam material according to claim 1 or 2, wherein: The particle size of the hollow glass microspheres is 50-100 μm.

8. The method for preparing a flame retardant sound absorbing foam material according to claim 1 or 2, wherein: The antioxidant is prepared by compounding DSTP and 1010 in a weight ratio of 2-4:1-3.

9. A flame retardant sound absorbing foam material, characterized in that: The method is described in any one of claims 1 to 8.

10. The use of the flame retardant sound absorbing foam material according to claim 9, characterized in that: Used in rail transportation, large shopping malls, and KTV venues.

Citation Information

Patent Citations

  • Sound absorption and thermal insulation polyolefin foamed sheet and preparation method thereof

    CN106046483A

  • Environment-friendly regenerated activated carbon and preparation method thereof

    CN117563562A

  • Heat-insulating and sound-absorbing light foaming material and preparation method thereof

    CN118480224A

  • Hierarchical pore sound-absorbing microsphere, preparation method thereof and sound-absorbing device

    CN119793344A

  • Ethylene-α-olefin copolymer for crosslinked foaming, resin composition for crosslinked foaming, and crosslinked foam prepared therewith

    JP2018162386A